KEDUDUKAN PERATURAN MENTERI TERHADAP PEMBENTUKAN PERATURAN DAERAH - Riski Riski (JURNAL AKTA YUDISIA, 2021)
Regional Regulation which in principle are formed in the context of carrying out government affairs which are the authority of the regions, in fact are considered to be contrary to ministerial regulation. This is because the position and content of the ministerial regulation has not been regulated in the Law on the formation of regulation, while the level of dynamics of change is very high and fast compared  to  local  regulations  whose  formation  is  influenced  by  political interests in the region and requires a long time. The problems discussed in this study were the legis ratio of the position of ministerial regulation according to Law  Number  12  of  2011  concerning  the  formation  of  regulations  and  the juridical implications of the position of ministerial regulation on the formation of regional regulations. This study aimed to determine the legis ratio of ministerial regulation according to Law Number 12 of 2011 concerning the formation of legislation and the juridical implications of the position of ministerial regulation on  the  formation  of  regional  regulations.  This  research  was  expected  to contribute thoughts both theoretically and practically to the dynamics of legal development in Indonesia. The research used normative juridical method that consisted of primary, secondary and non legal materials. From the results of the study it was concluded that, First, the position of ministerial regulation is a legislation that was formed based on the order of higher legislation (delegated legislation), while ministerial regulation which was formed based on authority is a policy regulation (Beleidsregel). Second, regional regulation must refer to and base their formation on ministerial regulation, if the ministerial regulations is formed based on the authority of attribution and/or delegation of the formation of legislation and its position contained in the hierarchy of statutory regulations and not formed based on the authority to administer government affairs (Bestuur). Keywords: Status of Regulations, Ministerial Regulation, Regional Regulation